Nkrumah's and Nyerere's Educational Visions - What Can Contemporary Africa Learn From Them? * - Abraham, Getahun (African Journal of Education and Practice, 2022)
Purpose: This study assesses the educational visions of Kwame Nkrumah and Julius Nyerere and what contemporary Africa can learn from their thoughts and visions. Methodology: A selective literature review was conducted of historical and contemporary academic texts of Nkrumah and Nyerere and other writers. Findings: The results show that Nkrumah and Nyerere emphasised the need for further educational development in their own and other countries in Africa. They also stressed relating education to the local reality and the relevance of adopting usable knowledge and experiences from other parts of the world. The instrumentality of education to change the life of the masses was given a vital place in their work. For Nkrumah and Nyerere, education should aim to create equity among the population instead of contributing to the rise of an elite class that prioritises its interests rather than the interests of society at large. They stressed that education should not be too theoretical at the expense of practical activities. A unique contribution to theory, practice and policy. The views and actions of Nkrumah and Nyerere have received criticism, but their visions are still relevant for contemporary Africa and beyond. I argue that those who are researching decolonisation and reform in education in African countries should consider reviewing the thoughts and visions of these pioneers. Their visions can lead to a better theoretical understanding to develop sustainable policies and practices that will alleviate the problems facing the individual countries as well as the continent.